2017
DOI: 10.1021/acs.jcim.6b00513
|View full text |Cite
|
Sign up to set email alerts
|

SQM/COSMO Scoring Function at the DFTB3-D3H4 Level: Unique Identification of Native Protein–Ligand Poses

Abstract: We have recently introduced the "SQM/COSMO" scoring function which combines a semiempirical quantum mechanical description of noncovalent interactions at the PM6-D3H4X level and the COSMO implicit model of solvation. This approach outperformed standard scoring functions but faced challenges with a metalloprotein featuring a Zn···S interaction. Here, we invoke SCC-DFTB3-D3H4, a higher-level SQM method, and observe improved behavior for the metalloprotein and high-quality results for the other systems. This meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 66 publications
1
59
0
Order By: Relevance
“…The SQM/COSMO scoring function consists of two terms. The first term is an interaction energy in the gas phase calculated with the self‐consistent charge density functional tight‐binding scheme, including the third‐order terms and the 3OB Slater‐Koster parameters, augmented with the dispersion, hydrogen‐bonding and halogen bonding corrections (SCC‐DFTB3‐D3H4X) . The second term is the desolvation free energy change upon binding, evaluated at the COSMO level from the PM6/COSMO calculation using MOPAC with default parameters .…”
Section: Computational Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SQM/COSMO scoring function consists of two terms. The first term is an interaction energy in the gas phase calculated with the self‐consistent charge density functional tight‐binding scheme, including the third‐order terms and the 3OB Slater‐Koster parameters, augmented with the dispersion, hydrogen‐bonding and halogen bonding corrections (SCC‐DFTB3‐D3H4X) . The second term is the desolvation free energy change upon binding, evaluated at the COSMO level from the PM6/COSMO calculation using MOPAC with default parameters .…”
Section: Computational Sectionmentioning
confidence: 99%
“…The time requirements were thus reduced from days to tens of minutes, which makes the SQM/COSMO SF applicable to drug design even in an industrial context. It was demonstrated that the SQM/COSMO SF outperformed standard SFs at the PM6‐D3H4X and DFTB3‐D3H4X (for Zinc metalloproteins) levels in identifying the native binding pose, which is a critical prerequisite for affinity estimation in physics‐based scoring . However, it was not clear whether the simplified SQM/COSMO SF could reliably estimate P‐L binding affinities and provide the valuable ranking for an inhibitor series.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of DFTB3 is most impressive for structural properties of metal compounds, while the energetics are less accurate, especially for highly charged ligands, due presumably to the limited description of polarization and charge-transfer effects. Even with the current set of parameters, nevertheless, DFTB models have been shown to be highly effective for the description of ligand binding to zinc-enzymes (Pecina et al, 2017); systematic improvement of DFTB models for more complex transition-metal ions remains a topic of major interest.…”
Section: Background On Computational Methodsmentioning
confidence: 99%
“…With corrections for London dispersion and hydrogen bonds, it is possible to achieve accuracy better than 1 kcal/mol in a wide range of noncovalent complexes of organic molecules . The resulting methods have also been successfully applied to large systems, such as to calculations of protein–ligand interactions in computer‐aided drug design . The issues encountered in dispersion and H‐bonds have been thoroughly studied, and while the present corrections are still not perfect, the current knowledge could be used for designing a new generation of more accurate SQM methods.…”
Section: Introductionmentioning
confidence: 99%